(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Determining the cut-off point value for muscle strength assessment to determine the risk of malnutrition in the elderly (≥ 60 years old) at Thong Nhat Hospital. Subject and method: A cross-sectional study was conducted in 260 elderly patients (≥ 60 years old) who visited the Outpatient clinic, Thong Nhat Hospital in October 2020. Results: The cut-off point value of muscle strength in assessing the risk of malnutrition for elderly patients visiting Thong Nhat hospital was 23.1 kilograms for men and 15.8 kilograms for women. There was a statistically significant relationship between the rate of malnutrition risk according to the cut-off point with nutritional status according to BMI (p=0.008), undernutrition according to arm circumference (p=0.002), functional impairment according to KATZ (p=0.004) and impaired cognitive function according to 6-CIT (p<0.001). Conclusion: Measurement of muscle strength in the assessment of nutritional status in the elderly is essential and a cut-off point value in assessing the risk of malnutrition is needed to be applied in clinical practice.